2012
DOI: 10.1038/sc.2012.51
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic pain on quality of life and depression in patients with spinal cord injury

Abstract: esign: A cross-sectional study. Objective: To assess the effects of pain on quality of life (QoL), functional independence and depression in patients with spinal cord injury (SCI). Setting: An inpatient rehabilitation center. Methods:A total of 140 patients (104 M, 36 F) with SCI who underwent inpatient rehabilitation treatment were examined. A questionnaire including clinical variables was applied. Motor score of Functional Independence Measure was used to assess dailylife activities, the 36-Item Medical Outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 24 publications
6
93
1
3
Order By: Relevance
“…23 However, neuropathic pain did not correlate with any other SF-36 subitems. It is reasonable that neuropathic pain did not correlate with all QOL factors, as SCI patients are affected not only by pain but also by limitations in moving, walking and controlling egestion and sexual function.…”
Section: Discussionmentioning
confidence: 93%
“…23 However, neuropathic pain did not correlate with any other SF-36 subitems. It is reasonable that neuropathic pain did not correlate with all QOL factors, as SCI patients are affected not only by pain but also by limitations in moving, walking and controlling egestion and sexual function.…”
Section: Discussionmentioning
confidence: 93%
“…Neuropathic pain places SCI patients at increased risk of depression [12,13] as well as lower self-ratings of mood and quality of life [14]. Additionally, depression and pain are rated as more severe when coinciding [15] with diagnosis and treatment of one being adversely affected by the other [16].…”
Section: Implications For Rehabilitationmentioning
confidence: 99%
“…[34][35][36][37] Several studies identified pain as an important factor that negatively affects depressive symptoms. [12][13][14][15][16] However, previous research addressed the impact on depression on the entire etiology of chronic SCI pain. The effect of isolated shoulder pain on depressive mood has not been investigated.…”
Section: The Influence Of Shoulder Pain On Depressionmentioning
confidence: 99%
“…[9][10][11] It has been reported that chronic pain is associated with higher levels of depressive symptoms in patients with spinal cord injury (SCI). [12][13][14][15][16] The chronic pain-related conditions that develop following SCI are heterogeneous. Although shoulder pain is recognized as the most common and incapacitating upper limb problem in patients after SCI, studies designed to investigate its effect on mood are lacking.…”
Section: Introductionmentioning
confidence: 99%